2017
DOI: 10.15294/kemas.v13i2.7896
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Stress on Urine Specific Gravity, Blood Pressure, and Heartbeat Among Underground Miners

Abstract: Underground miners highly exposed to thermal stress hazard. Closed condition, heavy work load, and limited ventilation are the common cause of high environment temperature in underground mining. Thermal stress can influence metabolism and physiological function of human body. The objective of these study is to investigate the effect of thermal stress to physiological (bodyweight, blood pressure, urine specific gravity, and heartbeat) of underground miners. This study is observational cross sectional study with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…values. Similar to a prior study which indicated that Australian workers who are miners working in an ambient temperature of 36.2°C result in 60% of workers working in a dehydrated condition [35]. Urinary Sp.…”
Section: Discussionsupporting
confidence: 83%
“…values. Similar to a prior study which indicated that Australian workers who are miners working in an ambient temperature of 36.2°C result in 60% of workers working in a dehydrated condition [35]. Urinary Sp.…”
Section: Discussionsupporting
confidence: 83%